2016
DOI: 10.1016/j.annemergmed.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Poor Outcomes After Emergency Department Discharge of the Elderly: A Case-Control Study

Abstract: Study objective The emergency department (ED) is an inherently high-risk setting. Our objective is to identify the factors associated with the combined poor outcome of either death or an ICU admission shortly after ED discharge in older adults. Methods We conducted chart review of 600 ED visit records among adults older than 65 years that resulted in discharge from any of 13 hospitals within an integrated health system in 2009 to 2010. We randomly chose 300 patients who experienced the combined outcome withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…A diagnosis of mental illness includes dementia, mood disorders, depression, and substance-related disorders. Although this is a different study with a different population, our finding in this study are similar to our prior work in that we found cognitive impairment 43 and chronic medical conditions 44 to be associated with a poor outcome after ED discharge in older adults. Patients with mental illness possibly have a diagnosis masked by the mental illness or are suffering an impairment in mental judgment and are unable to follow ED after care instructions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A diagnosis of mental illness includes dementia, mood disorders, depression, and substance-related disorders. Although this is a different study with a different population, our finding in this study are similar to our prior work in that we found cognitive impairment 43 and chronic medical conditions 44 to be associated with a poor outcome after ED discharge in older adults. Patients with mental illness possibly have a diagnosis masked by the mental illness or are suffering an impairment in mental judgment and are unable to follow ED after care instructions.…”
Section: Discussionsupporting
confidence: 88%
“…Second, as there have been several analyses in the past evaluating death after ED discharge, this analysis did not evaluate outcomes of death. 16,43 Also, the EDs at Kaiser Permanente Southern California do not represent the most overcrowded conditions (such as those seen at safety net hospitals) 45 and the uninsured and underinsured are not represented in this study. In addition, the data used for this analysis are from 2009–2010 and practices in admission after discharge may have changed since that time frame.…”
Section: Discussionmentioning
confidence: 95%
“…Our primary outcome was death within seven days after discharge from emergency departments, as in prior studies. 14 15 16 24 25 People admitted as inpatients, transferred out of the department, or discharged to palliative care or a hospice were ineligible for the outcome. In many US emergency departments, patients who require a period of observation for diagnostic testing or monitoring are billed under a specific “observation status.” These patients are subsequently discharged or formally admitted as inpatients, and, for the purposes of this study, we classified patients by this ultimate disposition (that is, admitted or discharged).…”
Section: Methodsmentioning
confidence: 99%
“…What could have been confounders in this population of the primary outcomes: "combined poor outcome of either death or an ICU admission shortly after ED discharge"? 1 C. This study was a case-control design. Why might investigators choose a case-control study design instead of a cohort study?…”
Section: Discussion Pointsmentioning
confidence: 99%